2012
DOI: 10.1111/j.1708-8305.2012.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Dengue Fever: Beware of Measles!: Table 1

Abstract: Febrile exanthema is a common symptom in returning travelers. In addition to cosmopolitan diseases, etiologies specific to the visited country must be considered. As an accurate diagnosis is important, clinical suspicion should be confirmed by laboratory tests. The case reports of three brothers returning from Indonesia highlight the possibility of misdiagnosis due to the clinical similarity and serological cross reactivity of dengue fever and measles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Both g:Profiler and TargetMine also detected the measles and influenza A pathways (hsa05162 and hsa05164, respectively). Measles and influenza are often listed as diseases that differ negligibly from DF in terms of their diagnosis4445. There are no DENV pathways in the Kyoto Encyclopedia of Genes and Genomes (KEGG) database.…”
Section: Discussionmentioning
confidence: 99%
“…Both g:Profiler and TargetMine also detected the measles and influenza A pathways (hsa05162 and hsa05164, respectively). Measles and influenza are often listed as diseases that differ negligibly from DF in terms of their diagnosis4445. There are no DENV pathways in the Kyoto Encyclopedia of Genes and Genomes (KEGG) database.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our results show that, even for samples collected within 7 days after onset of rash, 50% of the cases were negative for MeV RNA detection using real-time PCR. Since surveillance includes only the rubella infection as a differential diagnosis, which shows a very low incidence, the MoH in Morocco should consider other differential diagnoses, especially those spreading in our region, such as dengue fever[ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperendemic transmission of all four dengue serotypes, with cases of DHF, was present in Thailand, Vietnam, and Indonesia for over 40 years. Epidemic dengue reemerged in China during the 1980s & the 1990s after absence of several decades; associated with the first DHF occurrence in that country (Qiu et al, 1993) Nepal, the last country in the region to be affected, had the first cases detected in 2004. Dengue virus transmission occurred yearround, but typically reaches a seasonal peak which varies in timing from one country to another (for example, between June & November in Thailand, but between January & February in Indonesia).…”
Section: Introductionmentioning
confidence: 99%
“…But, without specific symptoms, febrile illness diagnosis in returning travelers was challenging. Pull et al (2012) reported that cosmopolitan infections such as measles must be considered, even more as its incidence was increasing in several parts of the world. Kutsuna et al (2015) reported that clinical manifestations, simple laboratory test results, and regions of travel are helpful to distinguish between dengue, malaria, and enteric fever in febrile returning travelers with non-specific symptoms.…”
Section: Introductionmentioning
confidence: 99%